Prevalence and Factors Associated with Reasons for looking for the Emergency Service at a Hospital in the Metropolitan Region of Curitiba-PR - Amato, Matheus; Ananias, Leonardo; da Silva, Franciele Cascaes; Nazário, Nazaré Otília (LAJEC - Latin American Journal of Emergency Care, 2022)
This study aims to identify the prevalence and factors associated with reasons for looking for the Emergency Service of a small hospital in the metropolitan area of Curitiba-PR. This is a cross-sectional observational study carried out between March and May/2021. Data collection was performed through analysis of medical records and interviews lasting 15 minutes with patients. Descriptive analysis was performed and the Pearson’s chi-square test was used to analyze the association between demographic characteristics and the most prevalent reasons for seeking out the ES, as well as Prevalence Ratio with its respective 95% confidence intervals. 170 patients participated in the study: male (52.9%), aged 18-30 years (41.2%), without a partner (52.4%), high school (63.5%), in occupational activity (52.4%). 82,3% were classified as little/not urgent and 75.9% were discharged after medical consultation. The most prevalent reasons for looking for the ES were respiratory symptoms (20%), trauma/injury (18.2%) and abdominal pain (10.7%). There was a statistically significant association between demographic characteristics, gender and age group with the most prevalent reasons for reaching out the ES. The conclusion was that the profile of users shows a slight predominance of males, young adults, active professionals and high-schoolers. The most prevalent reasons for looking for the ES were respiratory symptoms, trauma/injury and abdominal pain, with a higher prevalence of low/non-urgent care. The ES provides care predominantly for PHC, resulting from the patients’ low knowledge of the SUS care levels, predilection for the ES, fragility and inefficiency of the BHU.